2021
DOI: 10.3390/jcm10071441
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Drugs with Anti-Inflammatory Properties

Abstract: There is increasing evidence of sex differences in the action of anti-inflammatory drugs, with women being at significantly higher risk of adverse effects. Nevertheless, clinicians’ awareness of the implications of these sex differences on dosing and adverse event monitoring in routine practice is still in need of improvement. We reviewed the literature evaluating sex differences in terms of pharmacokinetics and pharmacodynamics of anti-inflammatory drugs. The anti-thrombotic activity of selective and non-sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 95 publications
3
22
0
2
Order By: Relevance
“…A 2021 systematic review and meta-analysis reiterated similar findings and revealed no negative association between use of NSAIDS, including Ibuprofen, with SARS-CoV-2 infection or its outcomes ( 39 ). Ibuprofen has been known to have a better analgesic response in men while higher threshold and greater tolerance for electrically induced pain, responded significantly to ibuprofen in contrast to women ( 40 ). Nevertheless, the high use of this drug during COVID-19 can be linked to its efficacy in relieving fever, infection ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 systematic review and meta-analysis reiterated similar findings and revealed no negative association between use of NSAIDS, including Ibuprofen, with SARS-CoV-2 infection or its outcomes ( 39 ). Ibuprofen has been known to have a better analgesic response in men while higher threshold and greater tolerance for electrically induced pain, responded significantly to ibuprofen in contrast to women ( 40 ). Nevertheless, the high use of this drug during COVID-19 can be linked to its efficacy in relieving fever, infection ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“… 23 24 Additional sex-specific differences in platelet function and neutrophil responsiveness have been suggested. 25 26 These findings indicate that there may be sex-related differences in inflammation-mediated thrombosis.…”
Section: Introductionmentioning
confidence: 78%
“… 24 Young females have more mature and responsive blood neutrophils and an elevated capacity of NET formation. 25 Moreover, female patients show a more pronounced formation of leukocyte-platelet aggregates and increased protease-activated receptor-1 mediated platelet reactivity. 39 Increased plasma level of MCP-1 in the female mice of the IL-17A group in this study supports that inflammation-mediated thrombosis might be more prominent in female mice than in male mice.…”
Section: Discussionmentioning
confidence: 99%
“…This over-the-counter medication is more effective in males than females, even though no pharmacokinetic differences between the sexes have been identified (14). However, pain receptors and nociception differences connected to estrogen activity in the nervous system might cause this variation in drug response (15). Even though several examples of sex-bias drug responses exist, most drug repurposing methods do not consider sex.…”
Section: Introductionmentioning
confidence: 99%